Spatial and Temporal Variability of Soil Redox Potential, pH and Electrical Conductivity across a Toposequence in the Savanna of West Africa - Bernard F. Tano; Casimir Y. Brou; Elliott R. Dossou-Yovo; Kazuki Saito; Koichi Futakuchi; Marco. C. S. Wopereis; Olivier Husson (Agronomy, 2020)
Soil redox potential is an important factor affecting soil functioning. Yet, very few agronomy studies included soil redox potential in relation to soil processes. The objective of this study was to evaluate the spatial and temporal variation in soil redox potential and to determine the soil parameters affecting its variation. Soil redox potential, soil moisture, soil temperature, pH and bulk electrical conductivity were measured in upland rice fields during two growing seasons at six positions along an upland–lowland continuum, including two positions at the upland, two at the fringe and two at the lowlands in central Côte d’Ivoire (West Africa). The measurements were made at the following soil depths: 3, 8, 20 and 35 cm. Soil redox potential varied between 500 and 700 mV at the upland positions, 400 and 700 mV at the fringe positions and 100 and 750 mV at the lowland positions, and increased with soil depth. Variations in soil redox potential were driven by soil moisture, bulk electrical conductivity and soil organic carbon. We concluded that for proper interpretation of soil redox potential, sampling protocols should systematically include soil pH, moisture and bulk electrical conductivity measurements.